1999
DOI: 10.1097/00002060-199903000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Stride Length and Walking Rate in Gait Training for Hemiparetic Stroke Patients1

Abstract: Sixty-three male hemiparetic patients in the recovery stage were examined to investigate the relationship between stride length and walking rate during computer-assisted gait training during a period of 4 wk. The maximum walking speed for 10 m was significantly increased from 32.3 to 53.2 m/min on average, and the stride length and walking rate also increased. However, the ratio of stride length to walking rate did not change significantly in 4 wk, with the mean value being 0.0068 m/steps/min, approximately on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 5 publications
2
31
0
1
Order By: Relevance
“…The aim of the functionally oriented manual physical therapy, which the patients received, is in restoration of preferred walking velocity and gait symmetry; however, different degree of asymmetries in kinematic and kinetic variables of hemiparetic gait are commonly seen after rehabilitation [3]. These results confirm previous observations showing an improved preferred walking speed as a result of rehabilitation treatment [20][21][22]. A significant increase was found in the gait velocity with a decrease in footprint peak times on both sides (with the exception of the 1st and the 6th trapezoids of the external footprint), more pronounced on the NS.…”
Section: Discussionsupporting
confidence: 82%
“…The aim of the functionally oriented manual physical therapy, which the patients received, is in restoration of preferred walking velocity and gait symmetry; however, different degree of asymmetries in kinematic and kinetic variables of hemiparetic gait are commonly seen after rehabilitation [3]. These results confirm previous observations showing an improved preferred walking speed as a result of rehabilitation treatment [20][21][22]. A significant increase was found in the gait velocity with a decrease in footprint peak times on both sides (with the exception of the 1st and the 6th trapezoids of the external footprint), more pronounced on the NS.…”
Section: Discussionsupporting
confidence: 82%
“…Suzuki et al (1999) reported an increase in walking speed from of 0.54 m s À1 to 0.89 m s À1 after four weeks of gait retraining over short distances. Burridge et al (1997) reported improvements in walking speed from 0.62 m s À1 to 0.73 m s À1 after a rehabilitation period using FES and physiotherapy.…”
Section: Methodsmentioning
confidence: 94%
“…The WR has rarely been used as a measure in routine clinical practice. There are a few available studies on stroke, Parkinson's disease, and knee-joint replacement, showing that the WR is decreased and can increase after rehabilitation and/or surgery (Andriacchi et al, 1997;Murray et al, 1978;Suzuki et al, 1999). There seems to be only one published study examining multiple sclerosis (MS; Paltamaa et al, 2008).…”
Section: The Walk Ratio In Pathological Gaitmentioning
confidence: 99%